The Florida "truth" anti-tobacco media evaluation: design, first year results, and implications for planning future state media evaluations. Issue 1 (1st March 2001) - Sly, David F; Heald, Gary R; Ray, Sarah
Abstract : OBJECTIVES: To outline the design and present selected findings from the evaluation of a state counter-advertising, anti-tobacco media campaign. The appropriateness of the design for states developing media evaluations is discussed. DESIGN: Four cross sectional, telephone surveys of the 12–17 year old population were used to track and monitor advertising and campaign awareness, confirmed awareness, and receptivity. The Florida baseline and one year surveys were used with two parallel national surveys in a quasi-experimental design to assess attitude and smoking related behaviour change attributable to the campaign. MEASURES: Awareness was measured by self report, confirmed awareness by unaided description, and receptivity by self reports of how well advertisements were liked, talked to friends about, and made one think about whether or not to smoke. Eleven attitude and three smoking behaviour items for Florida (treatment) and a national (control) population were compared at baseline and after 12 months. RESULTS: Significant increases in ad specific awareness, confirmed, receptivity, and campaign awareness, and confirmed awareness were reached by the sixth week. They continued to rise through the first year. No attitude and only minor behaviour differences were noted between the treatment and comparison populations at baseline. By the end of the first year, Florida youth had stronger anti-tobacco attitudes and better behaviour patterns than the comparison population. CONCLUSIONS: The industry manipulation strategy used in the Florida campaign resulted in high rates of recall, significant changes in attitudes/beliefs, and reduced rates of smoking behaviour among youth.